2002
DOI: 10.1128/aac.46.4.1125-1127.2002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Oral Artesunate and Dihydroartemisinin Antimalarial Bioavailabilities in Acute Falciparum Malaria

Abstract: Plasma antimalarial activity following oral artesunate or dihydroartemisinin (DHA) treatment was measured by a bioassay in 18 patients with uncomplicated falciparum malaria. The mean antimalarial activity in terms of the bioavailability of DHA relative to that of artesunate did not differ significantly from 1, suggesting that DHA can be formulated to be an acceptable oral alternative to artesunate.Drug resistance to Plasmodium falciparum is a growing problem in Southeast Asia (14). The artemisinin derivatives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 16 publications
3
31
1
Order By: Relevance
“…Comparisons of the pharmacokinetics of artesunate, artemether, and DHA have suggested that either oral DHA or artesunate provides greater antimalarial activity than similar doses of oral artemether in the combination treatment of uncomplicated falciparum malaria (10,14). This study suggests that intramuscular artemether has unfavorable pharmacokinetic characteristics in patients with uncomplicated malaria.…”
Section: Discussionmentioning
confidence: 79%
“…Comparisons of the pharmacokinetics of artesunate, artemether, and DHA have suggested that either oral DHA or artesunate provides greater antimalarial activity than similar doses of oral artemether in the combination treatment of uncomplicated falciparum malaria (10,14). This study suggests that intramuscular artemether has unfavorable pharmacokinetic characteristics in patients with uncomplicated malaria.…”
Section: Discussionmentioning
confidence: 79%
“…25 Patients unable to take oral medication were treated, as part of clinical trials to be reported separately, with parenteral artesunate or quinine. Intravenous artesunate (Guilin No.…”
Section: Treatmentmentioning
confidence: 99%
“…Dihydroartemisinin pharmacokinetics are very different; it has a small apparent volume of distribution of approximately 1.5 to 3.8 liters/kg, an oral clearance of approximately 1.1 to 2.9 liters/h/kg, and a very short terminal elimination half-life of approximately 0.83 to 1.9 h in adult patients (27,37,39,40). The population pharmacokinetic properties of the fixed oral combination of dihydroartemisinin and piperaquine have not been studied in pregnant women with malaria.…”
mentioning
confidence: 99%